Boosting Piezoelectricity under Illumination via the Bulk Photovoltaic Effect and the Schottky Barrier Effect in BiFeO3. Issue 5 (16th December 2021) - Heo, Yooun; Alexe, Marin
Abstract: Piezoelectricity is a key functionality induced by conversion between mechanical and electrical energy. Enhancement of piezoelectricity in ferroelectrics often has been realized by complicated synthetical approaches to host unique structural boundaries, so‐called morphotropic phase boundaries. While structural approaches are well‐known, enhancing piezoelectricity by external stimuli has yet to be clearly explored, despite their advantages of offering not only simple and in situ control without any prior processing requirement, but compatibility with other functionalities. Here, it is shown that light is a powerful control parameter to enhance the piezoelectric property of BiFeO3 single crystals. A series of measurements based on piezoresponse force microscopy and conductive atomic force microscopy, under illumination, reveal a locally enhanced effective piezoelectric coefficient, d zz, eventually showing almost a sevenfold increase. This phenomenon is explained with theoretical models by introducing the two main underlying mechanisms attributed to the bulk photovoltaic effect and Schottky barrier effect, involving the role of open‐circuit voltage and photocharge carrier density. These results provide key insights to light‐induced piezoelectricity enhancement, offering its potential for multifunctional optoelectronic devices. Abstract : Enhancement of piezoelectricity by external stimuli is advantageous for its simple and in situ control, and compatibility with other functionalities. In this work, light is shown to be a powerful control parameter to induce a sevenfold enhancement of piezoelectric coefficient in BiFeO3 single crystals due to the bulk photovoltaic and Schottky barrier effects, offering potential for multifunctional optoelectronic devices.